Mapping Management Patterns of Character Education Based on Local Wisdom - Rahmi Maulida; Suryadi Suryadi; Muh. Takdir; Syafa'at Ariful Huda (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study maps management patterns in local wisdom-based character education, identifies dominant value orientations, and examines their effects on student behavior and school climate in junior high schools. A Systematic Literature Review guided by PRISMA 2020 was conducted using Scopus data retrieved through Publish or Perish. Of 91 records identified, 14 articles met the inclusion criteria for thematic and bibliometric analysis. The findings show that local wisdom traditions such as Kawruh Pamomong, Siri’, Malee, Lonto Leok, and Panca Sthiti Dharmaning Prabu are implemented through school leadership, teacher–parent collaboration, and culturally responsive learning. These practices consistently emphasize honesty, discipline, religiosity, and social responsibility. Their implementation contributes to better student behavior, stronger socio-emotional development, and a more inclusive school climate. The review also reveals persistent gaps in methodological rigor, comparative studies, and explicit management frameworks. Overall, the study underscores the need for structured, measurable, and culturally grounded management models to strengthen character education in junior high schools.